1992
DOI: 10.3109/00365549209052636
|View full text |Cite
|
Sign up to set email alerts
|

A 56-month Prospective Surveillance Study on the Epidemiology of Aminoglycoside Resistance in a Belgian General Hospital

Abstract: In this survey, we studied the effect of extensive amikacin usage on the epidemiology of aminoglycoside resistance in a general hospital. The baseline resistance in the 12 months before amikacin was 5.8% for amikacin, 15.2% for gentamicin, 16.4% for tobramycin and 14.0% for netilmicin. During the following 44 months, amikacin was the aminoglycoside of first choice. In the first 2 years of this phase, resistance to amikacin did not change significantly. Later, amikacin resistance rose significantly, mainly due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The literature on the relationship between the use of aminoglycosides and the development of resistance is rather controversial and complex [25–28]. Some investigators reported increased AN resistance following unrestricted use of this compound [29–32]. However, it is difficult to conclude from those studies whether the use of AN was the only incriminating factor.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the relationship between the use of aminoglycosides and the development of resistance is rather controversial and complex [25–28]. Some investigators reported increased AN resistance following unrestricted use of this compound [29–32]. However, it is difficult to conclude from those studies whether the use of AN was the only incriminating factor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some hospitals report increased amikacin resistance with increased usage, while others do not (Gaynes etal. 1988;Nhieu and Collatz 1988;Jacoby et al 1990;Muscato et al 1991;King et al 1992;Maes and Vanhoof 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Since that early report, susceptibility to all of the major groups of anti-microbial agents has declined (8,10,26,31,47,76,77,107,111,121,122,230). In general, the prevalence of resistance to the ␤-lactam antibiotics, aminoglycosides, trimethoprim-sulfamethoxazole, and quinolones has increased with time, and this is associated with increased use of the respective drugs in a given environment (1,2,6,42,81,82,109,143). Increases in the prevalence of resistance to ␤-lactam antibiotics have been associated with increased use of the newer cephalosporins (11,12,37,42,48,73,109,110,158,159,164,193,234,239).…”
Section: Factors Associated With Resistancementioning
confidence: 99%
“…The first mechanism is most often involved in the resistance of Enterobacter spp. to ␤-lactam antibiotics and aminoglycosides, while the last two are most often involved in resistance to quinolones and trimethoprim-sulfamethoxazole (32,41,45,46,84,100,101,107,129,130,138,141,143,175,178,183,184,187,190,192,216).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%